The composition of the dental pellicle: an updated literature review - Enax, Joachim; Ganss, Bernhard; Amaechi, Bennett T.; Schulze zur Wiesche, Erik; Meyer, Frederic (Frontiers in Oral Health, 2023)
Background: The dental pellicle is a thin layer of up to several hundred nm in thickness, covering the tooth surface. It is known to protect the teeth from acid attacks through its selective permeability and it is involved in the remineralization process of the teeth. It functions also as binding site and source of nutrients for bacteria and conditioning biofilm (foundation) for dental plaque formation.Methods: For this updated literature review, the PubMed database was searched for the dental pellicle and its composition.Results: The dental pellicle has been analyzed in the past years with various state-of-the art analytic techniques such as high-resolution microscopic techniques (e.g., scanning electron microscopy, atomic force microscopy), spectrophotometry, mass spectrometry, affinity chromatography, enzyme-linked immunosorbent assays (ELISA), and blotting-techniques (e.g., western blot). It consists of several different amino acids, proteins, and proteolytic protein fragments. Some studies also investigated other compounds of the pellicle, mainly fatty acids, and carbohydrates.Conclusions: The dental pellicle is composed mainly of different proteins, but also fatty acids, and carbohydrates. Analysis with state-of-the-art analytical techniques have uncovered mainly acidic proline-rich proteins, amylase, cystatin, immunoglobulins, lysozyme, and mucins as main proteins of the dental pellicle. The pellicle has protective properties for the teeth. Further research is necessary to gain more knowledge about the role of the pellicle in the tooth remineralization process.